Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

(1+sin y)(1+sin (-y))=cos^2 y)

Sagot :

sin (-x) = - sin x
sin^2+cos^2=1

(1+siny)(1-siny)=cos^2y 
1-sin^2=cos^2y
cos^y=cos^2



[tex](1+siny)(1+sin(-y))=cos^2y\\\\L=(1+siny)(1-siny)=1^2-sin^2y=1-sin^2y=cos^2y\\\\R=cos^2y\\\\L=R[/tex]


[tex]sin(-x)=-sinx\\\\sin^2x+cos^2x=1\to1-sin^2x=cos^2x\\\\(a+b)(a-b)=a^2-b^2[/tex]